APPLICATION OF JEAN WATSON'S THEORY IN BREATHING EXERCISE INTERVENTION: A LITERATURE REVIEW - Metilda; Theophylia Melisa Manumara; Mohamad Aldi; Aulia Ramadhani; Siti Kania Ramadhany; Nisa Aulia Ervani; Siti Asiyah; Tiara Pebriyanti; Faruz Balqis Anasthasya; Rizma Rizkian Azzahra; Tasya nabila sari; Siti Salwa (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Background: Jean Watson's Caring Theoryemphasizes an empathetic and humanistic relationship between nurses and patients. This literature review aims to examine the application of this theory in breathing exercisesas a holistic approach to improving the physical and psychological conditionof patients. Method: The method used was a database searchon PubMed and Google Scholar with a publication periodrange of 2015-2025. Results: The results show that exercises such as slow deepbreathing, diaphragmatic breathing, progressive muscle relaxation,and finger hold relaxation are effective in reducing blood pressure and anxietyand improving lung function and quality of life. Conclusion: The collaborationbetween Jean Watson's Caring theory and breathing exercises can strengthen the holistic aspectof nursing, create a therapeutic environment, and accelerate the physical and psychological recoveryof patients.